Medroxyprogestogen enhances apoptosis of SKOV-3 cells via inhibition of the PI3K/Akt signaling pathway - Li, Yan (Editorial Department of Journal of Biomedical Research, 2013)
We sought to assess the effect of progestin on the apoptosis of epithelial ovarian cancer cell line SKOV-3 and via regulation of phosphorylation signaling in. Epithelial ovarian cancer cell line SKOV-3 was treated with medroxyprogestogen, phosphatidylinositol 3-kinase inhibitor LY294002 and vehicle control. Akt, phospho-Akt, Bcl-2 and phospho-Bad proteins were examined by immunoblotting assays. Medroxyprogestogen-induced apoptosis was assessed by MTT assays and Annexin V apoptosis assay. We found no significant difference in Akt and Bad expression in both the medroxyprogestogen groups and the control group. The levels of phospho-Akt, Bcl-2 and phospho-Bad were decreased in all the medroxyprogestogen groups and significantly decreased in the high dose mitogen-activated protein (MAP) group (10 µmol/L). Viability of SKOV-3 was reduced and apparent apoptosis of SKOV-3 cells was observed with increased doses of MAP. The findings suggest that medroxyprogestogen can induce SKOV-3 cell apoptosis by inhibiting Akt phosphorylation.